2015
DOI: 10.1111/1440-1630.12207
|View full text |Cite
|
Sign up to set email alerts
|

Occupational therapists' experiences of career progression following promotion

Abstract: This study is the first to address the common issues for occupational therapy staff around progression between grade levels. It therefore provides a basis for further research in other practice settings and for the development of supports for therapists climbing the career ladder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Convenience and small samples, in addition to low response rates, were frequently reported as a limitation, and affect the representativeness of the study population and, thereby, the validity and generalizability of the findings [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. In turn, small sample sizes were also reported to affect the statistical power [ 30 , 31 , 32 , 34 , 35 , 36 ]. Convenience samples with self-engaged participants, hence motivated to participate in a survey, can also result in skewed findings [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Convenience and small samples, in addition to low response rates, were frequently reported as a limitation, and affect the representativeness of the study population and, thereby, the validity and generalizability of the findings [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. In turn, small sample sizes were also reported to affect the statistical power [ 30 , 31 , 32 , 34 , 35 , 36 ]. Convenience samples with self-engaged participants, hence motivated to participate in a survey, can also result in skewed findings [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…From an organisational perspective, investment in early career program development may strengthen workforce development and create clearer pathways for career progression. Opportunities for the development of new skills and knowledge have been identified as a key retention factor for occupational therapists, both as new graduates (Cusick et al, 2004) and later in their careers (Nelson et al, 2015). The small number of early career programs and their relatively short tenure also presents a potential barrier to resourcing, due to challenges in reaching a ‘critical mass’ that makes their delivery cost effective.…”
Section: Discussionmentioning
confidence: 99%
“…For this study, early career was defined as the first 2 years of practice following graduation and employment at a Grade 1 level. The scope of practice for positions in early career programs (as classified in State Enterprise Agreements) is primarily limited to direct patient care and include significant oversight and support from more senior colleagues (Nelson et al, 2015). The objectives of the study were to:…”
Section: Key Points For Occupational Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in allied health have found that the highest qualification attained was a predictor of research generation [38], but all of the Masters qualified occupational therapists in this sample undertook those degrees as pre-registration qualifications (rather than as research training). The smaller increase in clinicians identifying themselves as research leaders may be related to the relatively fewer recognised leadership positions available in the profession [39]. While clinicians can attain research leadership at any stage of their career, via development of specialist skills and knowledge, they may still associate it with seniority in rank.…”
Section: Discussionmentioning
confidence: 99%